Detection of Aflatoxins in Rice Samples - Nisa, A; Zahra, N; Hina, S (Bangladesh Journal of Scientific and Industrial Research, 2015)
Aflatoxins are natural contaminants of cereals and other commodities throughout the world. Chronic dietary exposure even to low doses of aflatoxins is a known risk factor for liver cancer and effect protein metabolism and immunity. The study was carried out on a 1029 samples of brown rice, 1561 samples of white rice, 33 samples of broken rice, 13 samples of Sella rice, 52 samples of parboiled rice of export quality from Pakistan during the years 2006-2010 for determination of Aflatoxin B1, B2, G1 and G2 by Thin Layer Chromatography. 341 (33.13%) samples of white rice, 350 (22.42%) samples of brown rice, 13 (39.39%) samples of broken rice, 25 (24.27%) samples of Sella rice and 14 (26.92%) samples of parboiled rice were found contaminated with B1. B2 was detected in 33 (3.20%) samples of white rice, 23 (1.47%) samples of brown rice and 1(3.03%) samples of broken rice. While G1 is found in 9 (0.8%) samples of white rice, 57 (3.65%) samples of brown rice, 1 (1.5 %) samples of parboiled rice. Aflatoxin G2 was absent in all samples. DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22134 Bangladesh J. Sci. Ind. Res. 49(3), 189-194, 2014